The Nature and Scope of Religious Science in the View of Àyatullah JawÁdi Àmuli - Abd al-husayn Khusrawpanah; Qasim Babai (حکمت اسرا, 2011)
The topic of “religious science” is controversial and has its supporters and detractors. One of the supporters of “religious science” is ÀyatullÁh JawÁdÐ ÀmulÐ. In this debate the ÀyatullÁh takes “science” in its most general meaning to include all sciences and fields of knowledge, and sees religion as hierarchically subsuming all such sciences. He accepts the possibility of the existence of a religious science and uses both interpretive and philosophical methods to prove the same. With respect to the realization of religious science, he takes an absolutist approach and holds that religion covers and comprehends all sciences—there being no such thing as a “non-religious” science. Such a perspective is the result of a three stage process: 1) Determination of the central position of the intellect in the matrix of all religious understanding; 2) Validation of the universal reason and understanding of rational beings by religious Law; 3) Exposition of the universality of the sciences by recourse to textual evidence. When these three steps or stages are obtained, they progressively subsume all sciences and fields of knowledge.